2011
DOI: 10.1111/j.1740-0929.2010.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese consumer categorisation of beef into quality grades, based on Meat Standards Australia methodology

Abstract: The objective was to evaluate the sensory categorisation of beef by Japanese consumers, based on Meat Standards Australia methodology. Various cuts of beef, with a wide range of quality (from Australian and Japanese cattle) and three cooking methods (grill, yakiniku, shabu shabu), were evaluated by 1620 Japanese consumers in Tokyo and Osaka. Consumers rated each sample for four sensory attributes (tenderness, juiciness, flavor and overall satisfaction), then selected one of four grades (unsatisfactory/2-star, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 13 publications
5
30
0
1
Order By: Relevance
“…The degrees of freedom were determined using the Kenward and Rodger technique. The consumers were not expected to have much variation between countries on the basis of previous work Polkinghorne et al, 2011;Legrand et al, 2013). Individual base models were determined for the three different groups of data.…”
Section: Discussionmentioning
confidence: 99%
“…The degrees of freedom were determined using the Kenward and Rodger technique. The consumers were not expected to have much variation between countries on the basis of previous work Polkinghorne et al, 2011;Legrand et al, 2013). Individual base models were determined for the three different groups of data.…”
Section: Discussionmentioning
confidence: 99%
“…The best combinations to predict beef quality were however slightly different between cooking methods: Grill MQ4 score = 0.3 tenderness + 0.2 juiciness + 0.2 flavor and 0.3 overall liking, whereas shabu shabu MQ4 score = 0.2 tenderness + 0.2 juiciness + 0.4 flavor and 0.2 overall liking. These differences in weightings have little impact on the prediction accuracy given the high correlation between the different sensory scores (0.76-0.96; Polkinghorne et al, 2011). In the USA, the boundaries between categories were found to be ca.…”
Section: Meat Standards Australiamentioning
confidence: 99%
“…In terms of the Japanese consumer, Polkinghorne et al . () reported results on the sensory response of Japanese consumers to beef samples of a wide range of eating quality sourced from Japanese and Australian beef carcasses. The results showed that a single composite meat quality score (MQ4) could be created for the Japanese consumer response.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, a sub‐set of the data from Polkinghorne et al . (), where Japanese consumers had eaten the same Australian paired meat samples to the Australian consumers, were used in this study.…”
Section: Introductionmentioning
confidence: 99%